Microplastics Contamination of Mackerel and Red Snapper as Commercial Fish from the Takalar Fish Landing, Indonesia - Sita; Ilham; Yaqin, Khusnul; Ambeng (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Highlight Research 1. Microplastics were counted and identified based on their shape, size, and color 2. The particles were clarified using FTIR and confirmed to be microplastics based on the type of polymer. 3. The tissue destruction method is more effective with heating treatment. 4. Methods to prevent contamination are implemented so that the research results are guaranteed to be accurate. Abstract Microplastics can be ingested by marine organisms, including fish. Although it has been widely reported, further information regarding microplastic contamination in commercial fish is still needed. This study aimed to analyze the presence and concentration of microplastics in the digestive tract of the mackerel R. kanaguarta and red snapper L. gibbus and to identify the shape, size, color, and type of microplastic polymer. Digestion of the organic materials was performed using a 10% KOH solution, which was then filtered using a vacuum filtration system. The particles were observed using an Olympus microscope and clarified using FTIR. The results of the research showed that R. kanaguarta and L. gibbus landed at the Beba Fish Landing Base (PPI Beba) Takalar were contaminated with microplastics with a microplastic concentration in R. kanaguarta 0.21 ± 0.06 particles/g and L. gibbus 0.11 ± 0.04 particles/g. The microplastics found were fiber and fragment of varying colors, such as black, white, red, and yellow. The size of microplastics was dominant in the size class < 2 mm. The FTIR analysis confirmed the presence of polypropylene (PP), Ethylene/Propylene Copolymer, Nylon, Polyethylene terephthalate (PET), and polyester (PES). This study showed that both commercial fish species were contaminated with microplastics. These findings suggest that microplastics are widespread and contaminate commercial fish caught from Takalar waters. Further research is still needed on other seafood from this region, and analysis of polymer types such as FTIR is important to carry out as one of the standard methods in microplastic research.